Foundation design : theory and practice - Kameswara Rao, N. S. V. (Hoboken, N.J. : Wiley, 2010)
'Foundation Engineering focuses on the analysis and design of foundations using rational approaches to a large extent. Soil-Structure interaction approach using Winkler model for soil representation is discussed in detail along with conventional approach. It also presents the structural design methods using codes of practice for limit state design of RC structures. Analysis and design of commonly constructed shallow foundations as well as circular and annular foundations have been presented in detail. Pile foundations subjected to general loads and moments are discussed in detail.Presents updated design procedures in light of revised codes and standards, covering American Concrete Institute (ACI) codes Eurocode 7 Other British Standard-based codes Provides background material provided for easy understanding of the topics, such as: Code provisions for reinforced concrete Pile design and construction Machine foundations and construction practices Tests for obtaining the design parameters Covers subjects not covered in other foundation texts: Soil-structure interaction approaches using analytical, numerical, finite element methods Analysis and design of circular and annular foundations Analysis and design of Piles and groups subjected to general loads and movements Contains worked out examples to illustrate the analysis and design Provides several problems for practice at the end of each chapter Lecture materials for instructors available from the book's Companion Website'--
'Foundation Engineering focuses on the analysis and design of foundations using rational approaches to a large extent. Soil-Structure interaction approach using'--
Includes bibliographical references and index.
Keywords: Foundations